Macroprudential Policies for a Resource Rich Economy The Case of Mongolia - Maino, Rodolfo (IMF Working Papers; Working Paper ;, 2013)
This paper explores the extent to which macroprudential tools can be used to manage banking sector risks in Mongolia, a commodity producing country exposed to both procyclical and cross-sectional financial sector risks. Loose fiscal policy, rising credit activity, and heightened risk appetite-attributable to the commodity boom-are fuelling price volatility in asset markets, posing significant risks to financial stability if left unchecked. Rising interconnectedness, potential increase in dollarization and concentrated exposures are compounding those risks. Macroprudential tools can complement fiscal and monetary policy adjustments to avoid the buildup of vulnerabilities in the banking sector.